Myticalins: A Novel Multigenic Family of Linear, Cationic Antimicrobial Peptides from Marine Mussels (Mytilus spp.) - Leoni, Gabriele; De Poli, Andrea; Mardirossian, Mario; Gambato, Stefano; Florian, Fiorella; Venier, Paola; Wilson, Daniel; Tossi, Alessandro; Pallavicini, Alberto; Gerdol, Marco (Marine drugs, 2017)
The application of high-throughput sequencing technologies to non-model organisms has brought new opportunities for the identification of bioactive peptides from genomes and transcriptomes. From this point of view, marine invertebrates represent a potentially rich, yet largely unexplored resource for de novo discovery due to their adaptation to diverse challenging habitats. Bioinformatics analyses of available genomic and transcriptomic data allowed us to identify myticalins, a novel family of antimicrobial peptides (AMPs) from the mussel Mytilus galloprovincialis, and a similar family of AMPs from Modiolus spp., named modiocalins. Their coding sequence encompasses two conserved N-terminal (signal peptide) and C-terminal (propeptide) regions and a hypervariable central cationic region corresponding to the mature peptide. Myticalins are taxonomically restricted to Mytiloida and they can be classified into four subfamilies. These AMPs are subject to considerable interindividual sequence variability and possibly to presence/absence variation. Functional assays performed on selected members of this family indicate a remarkable tissue-specific expression (in gills) and broad spectrum of activity against both Gram-positive and Gram-negative bacteria. Overall, we present the first linear AMPs ever described in marine mussels and confirm the great potential of bioinformatics tools for the de novo discovery of bioactive peptides in non-model organisms.